IMPLEMENTASI APLIKASI E-VOTING PEMILIHAN KETUA BADAN EKSEKUTIF MAHASISWA (BEM) STMIK WIDYA UTAMA MENGGUNAKAN FRAMEWORK CODEIGNITER - Rianti Yunita Kisworini; M Hery Santoso; Yuniar Ode Yamin (LPPM STMIK Widya Utama, 2022)
Abstract – Voting is a term often used in elections and decision-makin in acommunity, agency, organization and country. This method will usually make it easier to determine the outcome and easier to agree on collectively. When an election is not in accordance with the agreement, voting can be used as a last resort. The election of the Chair of the Student Executive Board at STMIK Widya Utama is still done manually. Students who have the right to vote come to the polling stations then vote or tick the ballot papers and are collected into the ballot box. After the voting process was complete, the committee the began to count the votes. This study designed an E-voting application using the CodeIgniter Framework. This research produces a web application that can be accessed offline, has MD5 security and a more effective calculation so that this application can be accesse easily. This application also has qualified security in accordance with the benefits and purposes of research. In its development, this e-voting application applies the prototyping method which consists of several steps, namely identify basic requirements, develop initial prototype, user review and revice and echance the prototype. This application is tested using the Black Box Testing product test method which is valid and the benefit test is reliable. From the recapitulation of product test values and benefit tests, the highest percentages were obtained in the Useability and Efficiency aspects, namely 96.66% and 92.75%, which means that this e-voting application is easy to use and more efficient fot STMIK Widya Utama students.